Iridium-catalysed synthesis of C, N, N -cyclic azomethine imines enables entry to unexplored nitrogen-rich 3D chemical space - Almehmadi, YA; McGeehan, J; Guzman, NJ; Christensen, KE; Yamazaki, K; Dixon, DJ (Nature Research, 2024)
Three-dimensional nitrogen-rich bridged ring systems are of great interest in drug discovery owing to their distinctive physicochemical and structural properties. However, synthetic approaches towards N–N-bond-containing bridged heterocycles are often inefficient and require tedious synthetic strategies. Here we delineate an iridium-catalysed reductive approach to such architectures from C, N, N-cyclic hydrazide substrates using IrCl(CO)[P(OPh)3]2 and 1,1,3,3-tetramethyldisiloxane (TMDS), which provided efficient access to the unstabilized and highly reactive C, N, N-cyclic azomethine imine dipoles. These species were stable and isolable in their dimeric form, but, upon dissociation in solution, reacted with a broad range of dipolarophiles in [3 + 2] cycloaddition reactions with high yields and good diastereoselectivities, enabling the direct synthesis of nitrogen-rich sp3-hybridized pyrazoline polycyclic ring systems. Density functional theory calculations were performed to elucidate the origin of the diastereoselectivity of the cycloaddition reaction, and principal moment of inertia (PMI) analysis was conducted to enable visualization of the topological information of the dipolar cycloadducts.